1555 A Review of Safeguarding Documentation in Paediatric Trauma Patients. (October 2012) - Mirdin, A; Kent, A; Lindsay, AS; Vaidya, M; Parikh, A
Abstract : Background: The Royal London Hospital is a Major Trauma Center (MTC) in East London. In 2011, we saw approximately 300 paediatric traumas. Our borough has one of the highest rates of safeguarding issues in the country. Therefore, awareness and documentation of these issues is paramount. Aim: To determine the quality of safeguarding documentation in paediatric trauma patients presenting to the Major Trauma Centre (MTC). Methods: A retrospective analysis of documentation of paediatric trauma patients notes presenting to the Emergency Department at the Royal London Hospital between 1st January 2011 and 1st January 2012. A register of patients was obtained from the Emergency Department database and trauma database. There are no current UK guidelines regarding minimum standards of safeguarding documentation in the paediatric population in the UK. We defined the audit standard as the minimum level of documentation required to satisfy Barts Health NHS trust and local policies. Results: Projected results indicate safegaurding documentation may be inadequate in greater than 90% of cases. Conclusions: Current standards of safeguarding documentation within our Major Trauma Centre will be significantly below the minimum standard required at a local level. This has implications nationally where analysis would be expected to achieve a similar outcome.